تقرير أقل البلدان نمواً 2023 - United Nations Conference on Trade; Development (United Nations, 2024)
In 2023, the combined GDP of the LDCs was 10 per cent below the level it would have reached had the pre-pandemic (2010-2019) growth trend been sustained. As a result, at least an additional 15 million people in LDCs are now living in extreme poverty, with their governments severely constrained in their ability to sustain adequate investments in public services or invest in advancing development progress. The Report highlights the urgent need for concerted action to restore fiscal space in LDCs through the lasting resolution of the debt crisis, reform of the international financial architecture, and the mobilization of climate finance to enable needed investments towards low-carbon transition and green structural transformation. Without which, the SDGs and sustainable development cannot be realised. The Report advances several recommendations aimed at advancing the reform of global development finance, which in its current state, is deficient in terms of its quantity, quality, structure, cost and ease of accessibility. The Report also contains a detailed analysis of the possible role of central banks in shaping the financing of sustainable development and green structural transformation in LDCs. While the contribution of central banks to dealing with climate change has been discussed in developed countries, this is the first time this type of analysis is done in the context of the LDCs.